Análise ergonômica do trabalho: aplicação no setor de tratamento de águas em uma empresa de geração termelétrica - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The ergonomic assessment main goal is verifying the working conditions of a particular task. It is evidenced as a method of fundamental importance for a production system, not only providing comfort and security for workers, but enabling higher productivity from them, within creased profits and decreased losses, becoming a decisive factor for the company to stay in business, in such a competitive environment such as the current economic scenario. In this context, the present work searched, through the Ergonomic Work Analysis (EWA), propose appropriate e improvements enabling to at end the interests of the company and promote health and safety for workers. Thus a study was conducted in a company whose business is the generation of electricity, the water treatment sector, in the, located in the city of Candiota, Rio Grande do Sul. The ergonomic analysis of the work, which was structured in five stages: demand analysis, task analysis, activity analysis, diagnosis and improvement propositions. First, they identified the work situations are more critical. After, the activities were identified exercised officials, and evaluated postural, physical and environmental aspects such as noise, lighting and thermal comfort. Finally, improvement proposals were made under the ergonomics to minimize or eliminate the problems identified.
Keywords: Engenharia; Engenharia de produção; Ergonomia; Análise ergonômica do trabalho; Análise ergonômica; Avaliação postural; Análise de riscos; Termelétrica; Postura; Avaliação ergonômica; Candiota; CNPQ::ENGENHARIAS